Донецький гірничо-металургійний центр і виробничі центри східноєвропейського степу доби бронзи: порівняльний аналіз виробничої діяльності - Бровендер, Ю.М. (Археологія і давня історія України, 2021)
У статті на основі порівняльного аналізу джерел, що походять з гірничо-металургійних центрів епохи пізньої бронзи східноєвропейського степу, досліджених розкопками, визначається загальне і особливе в виробничій діяльності Донецького центру, активне функціонування якого пов’язується з носіями зрубної спільноти в її бережнівсько-маївській культурній традиції. Large-scale works have been carried out at the beginning of this century on the background of the set of Bronze Age monuments in the zone of Kartamysh copper ore occurrence in the Bakhmut basin of Donbass. Taking into account some previously researched monuments of mining and metallurgical activities within other ore occurrences of the Donetsk ridge, those works enable to compare the monuments of the Donetsk Mining and Metallurgical Center (DMMC) with other specialized monuments of Srubnaya cultural community in the copper ore territories of the Eastern European steppe. The monuments of Kartamysh archaeological microdistrict, as well as the other monuments of the Donetsk mining and metallurgical center, located in the zone of copper ore occurrences in the Bakhmut basin of Donbass, give evidences of all the cycles of ancient metal production. The majority of them are the evidence of the mining and ore-dressing cycle. Thus, the considerable volumes of mined and dressed ore, found in Kartamysh, as well as in other ore occurrences of the Bakhmut basin, currently suggest that the monuments in the ore territory of Donbass mainly operate within mining system. Similar specialization is observed in other mining and metallurgical areas in Eastern Europe, such as Mikhailo-Ovsyanka (Povolzhye) and Kargaly (South Ural). A feature of the DMMC is far lesser intensity of metallurgy and metalworking in its cultural frames. Limited range of DMMC monuments indicate that the production of metal products was focused only on domestic consumption. Fracturing of the Donbass bedrock, in contrast to the monolithic bedrock of Povolzhye, and especially to the Southern Urals, facilitated the effective use of stone tools in the process of mining. In the MMC, operating within the eastern production zone of the Srubnaya cultural community (Mikhailo-Ovsyanka, Kargaly), miners and metallurgists had to develop metallurgy more actively, since the features of geology in these regions required the use of metal tools to extract copper ores. Obviously, this circumstance explains a large number of end fragments of metal pickaxes found at Kargaly, as well as casting molds for casting these tools. The functioning of the full-scale cycle of ancient metal production and even visually recorded scale of ancient mining activity in the zone of copper ore occurrences of the Bakhmut basin gives reasons to assert the existence of mining and metallurgical center focused on large-scale production in the Donetsk Ridge in the Bronze Age. The main products of the DMMC were not metal items or even ingots, as it had been considered previously, but enriched copper ore (concentrate) as raw material for metallurgical production. Enriched ore was the commodity to be exchanged by the miners and metallurgists of the Donetsk center. It could be possibly done via professional traders with neighboring and distant tribes, and was exchanged for livestock and agriculture products, as well as for various household items. The analysis, carried out in the paper, proves that other mining and metallurgical complexes of the Eastern European steppe (Kargaly, Mikhailo-Ovsyanka), which had been previously explored, also operated at the same time and in similar to the DMMC production system.